FACTORS THAT ROLE IN DISCLOSURE OF LOCAL GOVERNMENT FINANCIAL REPORTS (LKPD) - Praptiningsih; Setiawan, Andy; Priyatno, Prima Dwi (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to analyze the factors that play a role in disclosing of local government financial statements (LKPD). The research was conducted because regions that had problems in disclosing Financial Statements in 2017-2019. The results of the audit of the Supreme Audit Agency (BPK), there were several LKPD problems, one of which occurred in South Kalimantan Province. Some several notes or findings were warned by BPK, including the management of fixed assets and inventories that were not prepared properly and the monitoring system of the APBD implementation which was still very low. This study aims to analyze the factors that play a role, including local government wealth, functional differentiation, audit findings, and financial independence. The population in this study were all regencies/cities in Kalimantan for the 2017-2019 period which consisted of 56 regencies/cities. The sample in this study used a census sample. Hypothesis testing in this study uses Multiple Regression Analysis with the SPSS program. The results of hypothesis testing show that (1) Local government wealth has a significant effect the disclosure of local government financial statements (2) Functional differentiation have a significant effect on disclosure of local government financial statements (3) Audit findings has a significant effect on disclosure, local government financial statements, (4) financial independence has a significant effect on disclosure, local government financial statements. With this research is hoped that the local government will made policies to increase the disclosure of LKPD to create good governance that is transparent between the government and the community.